Black tea preserves intestinal homeostasis through balancing barriers and microbiota in mice - Shi, Yuxuan; Guo, Shasha; Zhou, Jihong; Xu, Ping; Wang, Yuefei (Frontiers in Nutrition, 2024)
Introduction Black tea, a beverage consumed worldwide, possesses favorable effects on gastrointestinal tract, including nourishing stomach and promoting digestion. Nevertheless, its specific effects on intestinal homeostasis remains inconclusive. Methods We applied black tea to mice prior to inducing colitis with DSS and then monitored their body weight and disease activity index (DAI) daily. When sacrificed, we measured intestinal permeability and conducted analyses of mucin and tight junction proteins. We detected inflammatory cytokines, immune cells, and related inflammatory signaling pathways. In addition, the gut microbiota was analyzed through 16S rRNA sequencing, and the concentrations of short-chain fatty acids (SCFAs) were also measured. Results The results showed that black tea-treated group significantly rescued the DSS-disrupted intestinal structure. It reduced the relative abundance of the pathogenic bacterium Turicibacter, while increased the abundance of beneficial bacteria norank_f_Muribaculaceae and restored the contents of SCFAs such as acetate, propionate, and butyrate. It also protected the intestinal barrier by reducing the levels of immune response-related factors (e.g., TNF-α, IL-6, IL-1β) and increasing the expression of tight junction proteins (TJs) (e.g., ZO-1, occludin). Furthermore, black tea exhibited the capacity to suppress the expression of MMP-9 and ICAM-1, as well as to inhibit the activation of NF-κB signaling pathway. Discussion Our findings provide a theoretical framework that elucidates the mechanisms by which black tea preserves intestinal homeostasis, highlighting its potential as a preventive strategy against intestinal disruptions. This study contributes to the understanding of the dietary effects of black tea on gastrointestinal health.